Utilising virtual reality in alcohol studies: A systematic review. (March 2018) - Durl, James; Dietrich, Timo; Pang, Bo; Potter, Leigh-Ellen; Carter, Lewis
Background: The resurgence of interest in virtual reality (VR) in recent years has been exciting for health educators and researchers, yet little is known about VR's effectiveness. This systematic literature review aims to provide an overview of the prevalence of VR in alcohol studies and assess its effectiveness. Methods: Peer-reviewed articles were systematically searched from online databases including PubMed, ProQuest, Web of Science, ScienceDirect, Emerald, Ovid, Taylor & Francis and EBSCO. The grey literature and conference papers were excluded. Studies that passed the inclusion criteria were qualitatively assessed. Findings: Of the 1, 739 studies retrieved, 8 studies met the inclusion criteria. Three main applications of VR were found: (1) cue-exposure therapy, (2) driving simulators for examining relationships between alcohol and neurological activity and (3) training of healthcare professionals. Only one study focussed on adolescents, and only one study reported longitudinal outcomes. Conclusion: VR remains underutilised in alcohol studies. VR has shown positive results across the three applications focused on in this review. However, longitudinal evidence of effects and effectiveness remains limited and therefore limits the relevance of findings. More long-term empirical research is warranted.